Tinjuan Yuridis Terhadap Tanggung Jawab Atas Tindakan Hukum Anak Perusahaan Yang Merugikan Pihak Ketiga Oleh Induk Perusahaan Holding BUMN - Andwia Maharani; Elisatris Gultom (Hakim, 2024)
This research aims to study and determine the responsibilities of Holding as the parent company of SOE, if there is legal action taken by the subsidiary holding company which results in losses to third parties. Then, it is hoped that this research can be used as a reference for Holding as the parent company of SOE to see the limits of liability for losses to third parties resulting from legal actions of subsidiaries and also the solutions to resolve for similar problems. SOE has an important position in terms of supporting government programs that seek to realize prosperity and independence in balanced development. The method in this research was carried out in a normative juridical manner, so the research was based on applicable legal norms and carried out a review of the explanations contained in the library materials. It can be concluded from this research that the parent holding company will be responsible if the parent company participates in decision making.